VirBR, a transcription regulator, promotes IncX3 plasmid transmission, and persistence of bla NDM-5 in zoonotic bacteria - Ma, T; Xie, N; Gao, Y; Fu, J; Tan, CE; Yang, QE; Wang, S; Shen, Z; Ji, Q; Parkhill, J; Wu, C; Wang, Y; et al. (Nature Research, 2024)
IncX3 plasmids carrying the New Delhi metallo-β-lactamase-encoding gene, blaNDM-5, are rapidly spreading globally in both humans and animals. Given that carbapenems are listed on the WHO AWaRe watch group and are prohibited for use in animals, the drivers for the successful dissemination of Carbapenem-Resistant Enterobacterales (CRE) carrying blaNDM-5-IncX3 plasmids still remain unknown. We observe that E. coli carrying blaNDM-5-IncX3 can persist in chicken intestines either under the administration of amoxicillin, one of the largest veterinary β-lactams used in livestock, or without any antibiotic pressure. We therefore characterise the blaNDM-5-IncX3 plasmid and identify a transcription regulator, VirBR, that binds to the promoter of the regulator gene actX enhancing the transcription of Type IV secretion systems (T4SS); thereby, promoting conjugation of IncX3 plasmids, increasing pili adhesion capacity and enhancing the colonisation of blaNDM-5-IncX3 transconjugants in animal digestive tracts. Our mechanistic and in-vivo studies identify VirBR as a major factor in the successful spread of blaNDM-5-IncX3 across one-health AMR sectors. Furthermore, VirBR enhances the plasmid conjugation and T4SS expression by the presence of copper and zinc ions, thereby having profound ramifications on the use of universal animal feeds.